Assessment of Knowledge, Attitude and Practices of Allied Health Care Professional Students Towards Universal Precaution - Patond Swapnil1 Dakhode Sarika2 , Rawekar Alka3 , Pande Varsha4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A universal precaution is an approach to infection control to treat all human blood and certain human bodyfluids. History and examination cannot reliably identify all patients infected. Universal precautions areframed to prevent health care professionals who are exposed to various infections and by practicing variousbasic principles of infection control. A cross sectional survey was conducted to assess knowledge, attitudeamongst allied health care professional about universal precautions and to investigate their practicetowards universal precaution. First year Students of School allied health sciences, who were willing toparticipate included in the study. Study showed overall moderate knowledge among the students. Hencetraining sessions of universal precaution may need to be conducted regularly for these students. Awarenessamongst students can be achieved to maximum level by conducting awareness programs every year by theInfection control committee in the medical college.